Implementation of Pore Microstructure Model Generator and Pore Space Analysis Tools. (2015) - Putanowicz, Roman
Abstract: Mesoscale modelling of porous materials may require building explicit geometric models for porous microstructure. Such microstructure models are composed of connected voids (pores) embedded in an otherwise impermeable solid. Having such a model at hand it is possible to directly calculate several characteristics of the pore microstructure, for instance pore radii, pore lengths, pore wall surface area as well as spatial distribution statistics. Additionally, having a solver capable of simulating fluid flow through such model, it is possible to gain insight into the effects of pore microstructure characteristics on flow properties, both macroscopic, such as permeability, or microscopic, such as tortuosity. In their recent paper Hyman and Winter [1] discuss an algorithm for stochastic generation of explicit pore structures by thresholding Gaussian random fields. Unfortunately their paper is missing an discussion on effective implementation of the presented algorithm. In our paper we fill this void by providing detailed discussion on implementation side of the algorithm discussed by Hyman and Winter. Besides presenting a microstructure generator which we provide as Open Source program, this paper shows how generated model can exported to data formats suitable for analysis and visualisation with various tools, for instance data formats based on VTK library. The programs described in this paper can form a base for handy tools and reduce the programming effort of building simulation environment for materials microstructure analysis.